2020
DOI: 10.3390/nano10010105
|View full text |Cite
|
Sign up to set email alerts
|

Chloramine-T/N-Bromosuccinimide/FeCl3/KIO3 Decorated Graphene Oxide Nanosheets and Their Antibacterial Activity

Abstract: In this work, we report the synthesis of graphene oxide nanosheets (GO NS) using four different oxidants, namely, chloramine-T (CAT), FeCl 3 , N-bromosuccinimide (NBS), and KIO 3 . Fourier transform infrared spectroscopy (FTIR) was used to characterize the functional groups present in the synthesized GO. The microstructure analysis was performed using X-ray diffraction (XRD) and scanning electron microscopy (SEM) to investigate the morphology of GO. High-resolution transmission electron microscopy (HRTEM) stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…Nowadays, carbon materials, such as activated carbon [16], carbon nanotubes [17], graphene oxide nanoparticles [18][19] and nanocomposite [20] are extensively utilized as adsorbents given their high adsorption capacity. However, their costs can be very high, so their use is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, carbon materials, such as activated carbon [16], carbon nanotubes [17], graphene oxide nanoparticles [18][19] and nanocomposite [20] are extensively utilized as adsorbents given their high adsorption capacity. However, their costs can be very high, so their use is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ]; [ 23 ]; [ 29 ]; [ 60 ]; [ 61 ]; [ 62 ]; [ 63 ]; [ 64 ]; [ 65 ]; [ 66 ]; [ 99 ]; [ 106 ]; [ 110 ]; [ 111 ]; [ 120 ]; [ 122 ]; [ 130 ]; [ 131 ].…”
Section: Uncited Referencesunclassified
“…GO has a large precise floor vicinity, excessive electric mobility and excellent conductivity. GO exhibits several functional clusters on its boundaries and oxygen-containing functional groups that play a significant role in antimicrobial and antiviral efficiency [ [7] , [8] , [9] , [10] ]. The antibacterial efficacy of GO and its derivatives against gram-positive and gram-negative bacteria is remarkable [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[344,345] Furthermore, the oxidative characteristics of GO cause lipid peroxidation, which causes bacterial cell death. [346] Several scientific studies show that GO and its by-products can help fight the SARS-CoV-2 pandemic. [338,[347][348][349] Figerez et al recently reported the development of a triboelectric rechargeable respiratory mask with high filtration effectiveness (>95%) and low cost.…”
Section: Optical Sensorsmentioning
confidence: 99%